2021
DOI: 10.1073/pnas.2023348118
|View full text |Cite
|
Sign up to set email alerts
|

The number of catalytic cycles in an enzyme’s lifetime and why it matters to metabolic engineering

Abstract: Metabolic engineering uses enzymes as parts to build biosystems for specified tasks. Although a part’s working life and failure modes are key engineering performance indicators, this is not yet so in metabolic engineering because it is not known how long enzymes remain functional in vivo or whether cumulative deterioration (wear-out), sudden random failure, or other causes drive replacement. Consequently, enzymes cannot be engineered to extend life and cut the high energy costs of replacement. Guided by cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 73 publications
(125 reference statements)
0
68
0
Order By: Relevance
“…Moreover, by correlating k app of each condition with in vitro k cat we found most correlations to be poor in log scale ( Dataset S8 ). A recent study, using another proteomic dataset and a different GEM, also showed a poor correlation in log scale of R 2 = 0.27 between yeast k app and in vitro k cat at one condition ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, by correlating k app of each condition with in vitro k cat we found most correlations to be poor in log scale ( Dataset S8 ). A recent study, using another proteomic dataset and a different GEM, also showed a poor correlation in log scale of R 2 = 0.27 between yeast k app and in vitro k cat at one condition ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Turnover of another rapidly degrading protein, thiamin synthase (THI1), is explained by its suicide mechanism that means the enzyme has a single catalytic cycle before it is inactivated and needs to be replaced (Chatterjee et al, 2011;Joshi et al, 2020). Recently we showed across a wide range of enzymes in Arabidopsis, yeast and bacteria, that the number of catalytic cycles until replacement varied according to the chemical risk of the reaction they undertook, including enzymes with photoactivatable substrates or with reactive oxygen producing roles in metabolism (Hanson et al, 2021).…”
Section: Metabolic Explanation Of Increased Protein Turnover Ratesmentioning
confidence: 99%
“…The increased turnover of redox shuttling systems, namely glutathione and thioredoxin linked systems and the MDH enzymes involved in malate shuttles throughout the cell (Fig 4 ), may be due to increased flux through these pathways and thus a consequence of an increased rate of wear-out damage of these enzymes (Hanson et al, 2021;Tivendale et al, 2021).…”
Section: Metabolic Explanation Of Increased Protein Turnover Ratesmentioning
confidence: 99%
“…TTN values range from 1 (for suicide “enzymes” 131 ) to >10 7 . 132 No accepted scale of risk factors for enzyme reactivity has been established, although an early study suggested that reactions with O 2 or H 2 O 2 increased the risk of enzyme deactivation. 133 A more recent attempt to classify enzyme reaction risks suggested that radical mechanisms and those involving highly reactive intermediates increased the likelihood of enzyme deactivation.…”
Section: Biological Implicationsmentioning
confidence: 99%